A most peculiar book: the inherent strangeness of the Bible - Swenson, Kristin M. (Oxford University Press, Incorporated, 2021)
For a book that has consistently topped the best-seller lists since the invention of the modern printing press, the Bible remains wildly misunderstood. Inconsistencies and unexplained impossibilities are often set aside, with readers picking and choosing aphorisms and slogans at will. Such a pick-and-choose mentality is concerning, given the fact that the Bible remains influential in people's private lives and in public policy and discourse. Kristin Swenson's new book seeks to remind readers of the oddities and complications in the Bible, suggesting that those uncomfortable spots can offer remarkable opportunity for spiritual growth.